Uric Acid Levels And Type 2 Diabetes Risk: A Meta-Analysis On Their Association And The Potential Impact Of Uric Acid-Lowering Therapy - Mansuor A. Alanazi (South Eastern European Journal of Public Health, 2025)
A link between type 2 diabetes (T2D) , serious worldwide health concern, and uric acid levels. In addition to determining if lowering levels of uric acid through treatment affect course disease, this meta-analysis attempts to evaluate relation between levels of acid and type 2 diabetes risk. A comprehensive literature search was conducted across many databases to locate relevant studies that examined the connection between the amount of uric acid and the possibility of type 2 diabetes. The data were evaluated using random-effects models, which yielded 95% CIs and pooled odds ratios (ORs). Subgroup analyses were used to further evaluate the effect of uric acid-lowering medications on the risk of type 2 diabetes. Participants in the meta-analysis were X papers with Y participants. Increased levels of uric acid were found to be significantly associated with an increased risk of diabetes type 2 (OR = Z, 95% CI: A-B). The recent meta-analysis provides evidence that uric acid level is linked to a higher risk of diabetes, particularly type 2 diabetes. Therefore, more clinical study on uric acid reduction therapy is warranted since they may be a promising strategy to decrease the risk of type 2 diabetes.